Centaurs - Jeffrey, Gary (Jeffrey, Gary. Graphic mythical creatures., 2012)
Describes centaurs found in folklore, presents a graphic retelling of Hercules and the centaurs, and provides summaries of other tales featuring these mythical creatures.